2015
DOI: 10.1093/pcp/pcv006
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of CYP94 Family Gene Expression Alleviate the Jasmonate Response and Enhance Salt Tolerance in Rice

Abstract: The plant hormone jasmonate and its conjugates (JAs) have important roles in growth control, leaf senescence and defense responses against insects and microbial attacks. JA biosynthesis is induced by several stresses, including mechanical wounding, pathogen attacks, drought and salinity stresses. However, the roles of JAs under abiotic stress conditions are unclear. Here we report that increased expression of the Cyt P450 family gene CYP94C2b enhanced viability of rice plants under saline conditions. This gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 57 publications
3
74
1
Order By: Relevance
“…CYPs catalyze the biooxidation of various substrates through activation of molecular oxygen and play important roles in metabolic processes and stress responses 54 . It has been suggested that increased expression of CYP94 genes in rice plants alleviates jasmonate responses and enhances salt tolerance 55 . Mutation of CYP709B3 in Arabidopsis conferred sensitivity to ABA and low tolerance to salt stress, indicating that CYP709B3 plays a role in ABA responses and salinity tolerance 56 .…”
Section: Resultsmentioning
confidence: 99%
“…CYPs catalyze the biooxidation of various substrates through activation of molecular oxygen and play important roles in metabolic processes and stress responses 54 . It has been suggested that increased expression of CYP94 genes in rice plants alleviates jasmonate responses and enhances salt tolerance 55 . Mutation of CYP709B3 in Arabidopsis conferred sensitivity to ABA and low tolerance to salt stress, indicating that CYP709B3 plays a role in ABA responses and salinity tolerance 56 .…”
Section: Resultsmentioning
confidence: 99%
“…The pathway is modified from Arabidopsis, and genes that have been functionally confirmed or proposed in rice are shown in blue. Os OPR 7/Os08g0459600 (Tani et al ., ), Os JMT 1/Os05g0102000 (Qi et al ., ), Os JAR 1/Os05g0586200 and Os JAR 2/Os01g0221100 (Wakuta et al ., ), and CYP 94C2b/Os12g0150200 (Kurotani et al ., ). (b) OPDA , JA , and JA ‐Ile contents of 6‐wk‐old glasshouse‐grown wild‐type ( WT ) and llb plants.…”
Section: Resultsmentioning
confidence: 97%
“…Loss of LLB function resulted in a pleiotropic phenotype including increased hypersensitive response (HR)-like lesion formation and lamina bending, constitutive expression of stress/defence related genes, enhanced resistance to fungal and bacterial pathogens, elevated jasmonic acid (JA) and brassinosteroid (BR) accumulation/signalling, The pathway is modified from Arabidopsis, and genes that have been functionally confirmed or proposed in rice are shown in blue. OsOPR7/Os08g0459600 (Tani et al, 2008), OsJMT1/Os05g0102000 (Qi et al, 2015), OsJAR1/ Os05g0586200 and OsJAR2/Os01g0221100 , and CYP94C2b/Os12g0150200 (Kurotani et al, 2015). (b) OPDA, JA, and JA-Ile contents of 6-wk-old glasshouse-grown wild-type (WT) and llb plants.…”
Section: Llb Represses Stress and Defence Responsesmentioning
confidence: 99%
“…Rice growth and development was affected by adverse environment. Overexpression of PtCYP714A3, OsDSS1 and CYP94C2b could improve rice tolerance to drought and salt stress (Kurotani et al, 2015; Tamiru et al, 2015; Wang et al, 2016). Here, we confirmed that OsCYP71D8L conferred rice with better tolerance to drought and salinity stress.…”
Section: Resultsmentioning
confidence: 99%